Sociedad del conocimiento y la economía - Terán - Cano, Fabián (2018)
The main contribution of this article is the characterization of the knowledge society, its origins and interrelationships, and its transit towards what is called new economy, which means that not only goods that look for an income are produced; but it produces ideas that based on this new knowledge and innovation allow to transform the productive ideas to reach the economic development by overcoming the permanent problems of justice and inequality.Moreover, in this document it is carried out the contextualization of the knowledge society meaning through the highlighting of the conceptual aspects related to technology innovation and the economy knowledge, by means of placing an outline of the Ecuadorian case in the globalization stage at the end.An analysis is made of the knowledge economy or new economy that is related to thetechnological advances that information technology provides through the communication networks that are developed as part of the so-called globalization process, and is related to the progress made in the Ecuador as part of the objectives of the National Plan for Good Living, and the very interaction of the economy with the world.